Pulmonary thromboembolism – A rare complication in a scrub typhus infection - Tarapada Ghosh (IDCases, 2020)
We describe a rare haematological complication of pulmonary thromboembolism in a scrub typhus infection. There are very few case reports on scrub typhus infection causing deep venous thrombosis. Vasculitis and perivasculitis with endothelial dysfunction could be considered as the main pathologic mechanism causing this complication.